Video-Based Microsurgical Education versus Stationary Basic Microsurgical Course: A Noninferiority Randomized Controlled Study - Dąbrowski, Filip; Stogowski, Piotr; Białek, Jan; Fliciński, Filip; Piotrowski, Maciej; Pankowski, Rafał; Ceynowa, Marcin; Rocławski, Marek; Wałejko, Szymon; Mazurek, Tomasz (Journal of Reconstructive Microsurgery, 2022)
Background Repetitive training is essential for microsurgical performance. This study aimed to compare the improvement in basic microsurgical skills using two learning methods: stationary microsurgical course with tutor supervision and self-learning based on digital instructional materials. We hypothesized that video-based training provides noninferior improvement in basic microsurgical skills.Methods In this prospective study, 80 participants with no prior microsurgical experience were randomly divided into two groups: the control group, trained under the supervision of a microsurgical tutor, and the intervention group, where knowledge was based on commonly available online instructional videos without tutor supervision. Three blinded expert microsurgeons evaluated the improvement in basic microsurgical skills in both groups. The evaluation included an end-to-end anastomosis test using the Ten-Point Microsurgical Anastomosis Rating Scale (MARS10) and a six-stitch test on a latex glove. Statistically significant differences between groups were identified using standard noninferiority analysis, chi-square, and t-tests.Results Seventy-seven participants completed the course. Baseline test scores did not differ significantly between groups. After the 4-day microsurgical course, both groups showed statistically significant improvement in microsurgical skills measured using the MARS10. The performed tests showed that data for self-learning using digital resources provides noninferior data for course with surpervision on the initial stage of microsurgical training (7.84; standard deviation [SD], 1.92; 95% confidence interval [CI], 7.25–8.44) to (7.72; SD, 2.09; 95% CI, 7.07–8.36).Conclusion Video-based microsurgical training on its initial step provides noninferior improvement in microsurgical skills to training with a dedicated instructor.
Keywords: microsurgery; microsurgical training; COVID-19; online training; microvascular anastomosis